Development of renewable energy potential in Kuwait - Muhaisen, Naser; Ahmed, Musse Mohamud; Khan, Sheroz; Habaebi, Mohamed Hadi; Ahmed, Nabil; Arshad, Atika (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper is aimed at proposing an effective solution to enhance continuous power availability and to reduce the peak load demand in Kuwait electric grid system. The peak demand is made from solar renewable energy sources. The potential renewable energy as power generation sources in Kuwait has been studied and solar energy potential has been analyzed. In the pursuit of proposing hybrid system based of solar and wind, this paper only discusses the solar energy part. In this paper solar energy system performance has been simulated using PSIM software in order to see the real justification of utilizing it as alternative solution to Kuwait electricity demand during peak hours of a hot summer day.